Cu(II) complexes with 4-amino-3, 5-dimethyl isoxazole and substituted aromatic aldehyde Schiff bases: synthesis, crystal structure, antimicrobial activity, DNA binding and cleavage studies. Issue 8 (18th April 2017) - Pradeep Kumar, Marri; Vamsikrishna, Narendrula; Ramesh, Gali; Subhashini, N. J. P.; Nanubolu, Jagadeesh Babu; Shivaraj
Abstract: Three isoxazole Schiff bases 2-((E)-(3, 5-dimethylisoxazol-4-ylimino)methyl)-6-methoxyphenol (L 1 ), 2-((E)-(3, 5-dimethylisoxazol-4-ylimino)methyl)-4, 6-diiodophenol (L 2 ), 2-((E)-(3, 5-dimethylisoxazol-4-ylimino)methyl)-6-bromo-4-chlorophenol (L 3 ), and their Cu(II) complexes [Cu(L 1 )2 ] (1 ), [Cu(L 2 )2 ] (2 ) and [Cu(L 3 )2 ] (3 ) were synthesized. All the complexes have been characterized by elemental analysis, FT-IR, ESI mass, UV-Visible, ESR, TGA, magnetic moments, and single-crystal X-ray diffraction analysis. Based on analytical data, a square planar geometry is assigned to the Cu(II) complexes with N2 O2 donors from the Schiff base ligands. The single-crystal X-ray diffraction measurements of1 and2 confirmed the square planar geometry. DNA binding studies from electronic absorption titrations, viscosity measurements, and fluorescence quenching studies indicated an intercalation mode of binding of Cu(II) complexes with CT-DNA. DNA cleavage experiments of Cu(II) complexes with supercoiled plasmid pBR322 DNA have also been investigated by agarose gel electrophoresis in the presence of H2 O2 (oxidative cleavage) and UV light (photolytic cleavage). The synthesized compounds were screened for antibacterial ( Escherichia coli, Pseudomonas putida, Klebsiella pneumoniae, Bacillus subtillis and Staphylococcus aureus ) and antifungal ( Candida albicans and Aspergillus niger ) activities by the paper disk method. The Cu(II) complexes showed better activity than corresponding Schiff bases. Abstract :